1992
DOI: 10.1109/16.108233
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of transient temperature uniformity in RTP systems

Abstract: Independent, dynamic control of multiple lamps in a rapid thermal processing (RTP) system is a potential solution to the problem of transient wafer temperature nonuniformity. This brief presents a technique based on linear programming for minimization of worst-case error during temperature trajectory following, given a model of an axisymmetric, multi-lamp RTP system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…But the optimal location of heating lamps can be determined by steady optimization. If the locations of lamps are determined, the unsteady lamp power profile can be optimized by multivariable control [5]. So the scope of this study is confined to steady state.…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…But the optimal location of heating lamps can be determined by steady optimization. If the locations of lamps are determined, the unsteady lamp power profile can be optimized by multivariable control [5]. So the scope of this study is confined to steady state.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…They concluded that the radiative heat transfer by reflection had an insignificant effect on the heat transfer result of RTP and heat loss and that convective heat transfer must be considered to obtain uniform temperature distributions on the wafer surface. Norman [5,6] conducted studies for wafer uniformity in steady state and transient state by multivariable control of heating lamps. There are few studies on finding the optimum positions and temperatures of heating lamps for uniform temperature distribution on the wafer surface.…”
Section: Introductionmentioning
confidence: 99%
“…Before concluding this section, let us mention a different optimization formulation for the CVD furnace problem proposed by Norman [9] [lo]. He did not try to solve the full optimal control problem as we are.…”
Section: -mentioning
confidence: 99%
“…In [6], Norman formulates the RTP feedforward trajectory generation problem as a convex optimization problem wit.h various linear constraints and a quadratic objective function. In this section, we first elaborate those linear constraints and define a suitable quadratic objective function.…”
Section: Feedforward Control Designmentioning
confidence: 99%